PATH-03. CLINICAL UTILITY OF NEXT GENERATION SEQUENCING IN IDH-WILDTYPE GLIOBLASTOMA: THE DANA-FARBER CANCER INSTITUTE EXPERIENCE. (9th November 2020) - Jane Lim-Fat, Mary; Youssef, Gilbert; Touat, Mehdi; Iorgulescu, Bryan; Woodward, Eleanor; Whorral, Sydney; Allen, Marie; Vogelzang, Jayne; Pisano, William; Rahman, Rifaquat; Chukwueke, Ugonma; Mcfaline-Figueroa, Jose; et al.
Abstract: BACKGROUND: Comprehensive next generation sequencing (NGS) is available through many academic institutions and commercial entities, and is incorporated in practice guidelines for glioblastoma (GBM). We retrospective evaluated the practice patterns and utility of incorporating NGS data into routine care of GBM patients at a clinical trials-focused academic center. METHODS: We identified 1, 011 consecutive adult patients with histologically confirmed GBM with OncoPanel testing, a targeted exome NGS platform of 447 cancer-associated genes at Dana Farber Cancer Institute (DFCI), from 2013-2019. We selected and retrospectively reviewed clinical records of all IDH -wildtype GBM patients treated at DFCI. RESULTS: We identified 557 GBM IDH -wildtype patients, of which 227 were male (40.7%). OncoPanel testing revealed 833 single nucleotide variants and indels in 44 therapeutically relevant genes (Tier 1 or 2 mutations) including PIK3CA (n=51), BRAF (n=9), FGFR1 (n=8), MSH2 (n=4), MSH6 (n=2) and MLH1 (n=1). Copy number analysis revealed 509 alterations in 18 therapeutically relevant genes including EGFR amplification (n= 186), PDGFRA amplification (N=39) and CDKN2A/2B homozygous loss (N=223). Median overall survival was 17.5 months for the whole cohort. Seventy-four therapeutic clinical trials accrued 144 patients in the upfront setting (25.9%) and 203 patients (36.4%) at recurrence. Altogether, NGS data for 107 patients (19.2%) were utilized for clinical trial enrollment or targeted therapy indications. High mutational burden (>17mutations/Mb) was identified in 11/464 samples (2.4%); of whom 3/11 received immune checkpoint blockade. Four patients received compassionate use therapy targeting EGFRvIII (rindopepimut, n=2), CKD4/6 (abemaciclib, n=1) and BRAF V600E (dabrafenib/trametinib, n=1). CONCLUSION: While NGS has greatly improved diagnosis and molecular classification, we highlight that NGS remains underutilized in selecting therapy in GBM, even in a setting where clinical trials and off-label therapies are relatively accessible. Continued efforts to develop better targeted therapies and efficient clinical trial design are required to maximize the potential benefits of genomically-stratified data.